High-performance copper-free resin-based brake material prepared from red mud

By using red mud to replace copper powder in resin-based braking materials, combined with raw materials such as phenolic resin, bamboo fiber and alumina, high-performance copper-free resin-based braking materials are prepared, which solves the problem of heavy metal pollution in existing materials and achieves high performance and green and sustainable development of the materials.

CN119613014APending Publication Date: 2025-03-14FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411792365.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The dust generated by existing resin-based braking materials contains a large amount of heavy metal components, such as copper elements, which harms the environment and human health. At the same time, the thermal conductivity of copper improves the material's thermal decay resistance, but it is difficult to take into account both green and high performance.

Method used

Red mud is used to replace copper powder in resin-based braking materials, and high-performance copper-free resin-based braking materials are prepared by combining red mud as filler with phenolic resin, bamboo fiber, alumina and other raw materials.

Benefits of technology

It realizes the high performance of copper-free resin-based brake materials, including good friction and wear performance and heat fading resistance, while reducing material costs and turning waste into treasure, which has the significance of green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613014A_ABST
    Figure CN119613014A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance copper-free resin-based braking material prepared from red mud. The high-performance copper-free resin-based braking material is prepared from the following raw materials in percentage by mass: 30-40 wt% of red mud, 15-25 wt% of resin, 5-9 wt% of bamboo fibers, 15-25 wt% of aluminum oxide, 0-20 wt% of barium sulfate, 5 wt% of tire powder and 3 wt% of graphite. The red mud is adopted to replace copper which is harmful to the environment and high in cost in the brake material, the heat fading resistance of the friction material is improved due to the fact that the red mud has good high-temperature volume stability, and the material cost is effectively reduced while non-metallization of the brake material is achieved. The method has important significance on green and sustainable development of the aluminum manufacturing industry and the braking material industry in China, and has good engineering application value and remarkable economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of brake materials, and in particular relates to a high-performance, copper-free, and environment-friendly resin-based brake material prepared by using red mud. Background Art

[0002] With the development of the times and the acceleration of people's pace of life, the running speed of vehicles is also steadily increasing. The braking system, as one of the key components in the car, has attracted much attention from researchers. The development process of resin-based brake materials has gone through the asbestos friction material stage, the semi-metal friction material stage, the asbestos-free organic friction material stage and the copper-free friction material stage. Resin-based brake materials are composed of binders, reinforcing components, fillers and friction performance regulators. In recent years, people have found that the dust generated during the braking process contains a large amount of heavy metal components, such as copper and zinc. Especially for friction materials containing copper elements, copper-containing dust is discharged into the environment during the braking process, and some dust is suspended in the air, which is harmful to human health; some dust flows into the soil and rivers with rainwater, causing harm to microorganisms and the environment. However, copper has good thermal conductivity, which can transfer the heat generated during the braking process in time, improving the thermal decay resistance of the brake material; it also has high-temperature solid lubrication, which is beneficial to reduce the self-loss of the friction material and improve the stability of the friction coefficient. Therefore, how to ensure that the resin-based brake material is copper-free while making it both green and high-performance has become a key research topic for new resin-based brake materials in recent years.

[0003] Red mud is an industrial solid waste discharged when the aluminum industry extracts alumina. Its main components are silicon dioxide, calcium oxide, ferric oxide, aluminum oxide, sodium oxide, etc. The particle diameter of red mud is 0.088-0.25 mm, the specific gravity is 2.7-2.9, and the melting point is 1200-1250°C. For every ton of alumina produced, about 1.0-1.8 tons of red mud are discharged. As the largest aluminum producer, China discharges hundreds of millions of tons of red mud each year, with a cumulative stockpile of about 1.1 billion tons, covering an area of ​​more than 120,000 acres. In the present invention, it is applied to brake materials to replace copper powder in brake materials, which can not only improve the performance of brake materials and turn waste into treasure, but also has important significance for the green and sustainable development of my country's aluminum industry and brake materials.

[0004] At present, the recycling of red mud is mainly applied to the fields of construction and paving materials, mine filling materials, antifouling coatings, adsorbents, etc. For example, the patent "A high-iron red mud dealkalization resource utilization process and its application" (CN202410616614.6) converts high-iron red mud into harmless tailings, which is applied to the fields of construction and paving materials; the patent "A red mud high-doped hazardous waste solidification filling material and its preparation method" (CN202410563546.1) prepares high-performance red mud-based filling materials with high fluidity, early strength and fast hardening, and low water bleeding rate, which are used in the field of mine filling; the patent "A method for preparing an alkaline red mud coating for preventing marine biological attachment" (CN202310552335.3) fully mixes stearic acid, anhydrous ethanol, and red mud powder to obtain hydrophobic red mud. Powder, used to prepare antifouling coatings, forming alkaline red mud coatings that prevent marine organisms from attaching; the patent "A method for preparing composite materials by doping red mud with carbide slag" (CN202410558054.3) roasts red mud to obtain modified red mud, and adds carbide slag powder, sulfur source, activator, water, etc. to mix and stir, and further hydrothermally reacts to obtain an adsorbent with good adsorption effect on mercury; the patent "A composite material filled with polydimethylsiloxane" (CN202311362866.2) prepares red mud / polydimethylsiloxane composite materials, and uses red mud as a cross-linking node to improve the elastic modulus and impact strength of the composite material. At present, there is no case of applying red mud in the field of brake materials. Therefore, the present invention uses red mud to prepare high-performance copper-free resin-based brake materials, and uses red mud to replace copper that is harmful to the environment and has a high cost, so as to achieve the metal-free brake material while reducing the material cost, turning waste into treasure, and has high innovation and engineering application value. Summary of the invention

[0005] The purpose of the invention is to use red mud to replace copper powder in a resin-based brake material to prepare a high-performance copper-free resin-based brake material.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A high-performance copper-free resin-based brake material prepared from red mud is made of the following raw materials in percentage by mass: 30-40wt% of red mud, 15-25wt% of resin, 5-9wt% of bamboo fiber, 15-25wt% of aluminum oxide, 0-20wt% of barium sulfate, 5wt% of tire powder, and 3wt% of graphite, the sum of the percentages by mass of each raw material being 100%.

[0008] Furthermore, the mesh size of the red mud is 100 to 200 meshes.

[0009] Furthermore, the resin is phenolic resin.

[0010] The preparation of the resin-based brake material comprises the following steps:

[0011] 1) Processing of bamboo fibers: Shearing the bamboo fibers to obtain bamboo fibers with a length of less than 20 mm;

[0012] 2) Drying of raw materials: Dry the resin, sheared bamboo fiber, and tire powder at 60°C for 30 minutes, and dry the red mud, alumina, barium sulfate, and graphite at 120°C for 60 minutes.

[0013] 3) Evenly mix the materials: weigh the dried raw materials according to the corresponding proportions and stir them for a short time at a high frequency to ensure that the materials are evenly mixed;

[0014] 4) Hot pressing: placing the uniformly mixed material obtained in step 3) into a pre-heated mold and performing dry hot pressing;

[0015] 5) Heat treatment: The sample obtained by hot pressing is heat treated at 160° C. for 12 hours and then cooled in the furnace to obtain the high-performance copper-free resin-based brake material.

[0016] Furthermore, the total stirring time of the short-term high-frequency stirring in step 3) is 5 to 8 minutes, and the stirring time each time does not exceed 10 seconds.

[0017] Furthermore, in step 4), the temperature of the hot pressing molding is 165° C., the pressure is 10 MPa, the holding time is 6 min, and the exhaust is performed 2 to 3 times during the holding time.

[0018] Furthermore, the friction coefficient of the resin-based brake material at 300-350° C. is above 0.45.

[0019] Furthermore, the Box-Behnken design method was used to optimize the formula of resin-based brake materials, analyze the interaction between red mud and resin matrix, reinforcing fiber and filler, and obtain the optimized formula of high-performance copper-free resin-based brake materials.

[0020] The obtained resin-based brake material does not contain copper and other heavy metal components harmful to human body.

[0021] The beneficial effects of the present invention are:

[0022] (1) Red mud is an industrial solid waste discharged when the aluminum industry extracts alumina. Its main components are silicon dioxide, calcium oxide, ferric oxide, aluminum oxide, sodium oxide, etc. It has good heat resistance and high-temperature volume stability, high specific surface area, good adsorption performance, etc. Applying it to brake materials can not only improve the performance of brake materials, but also make use of waste resources. It is of great significance to the green and sustainable development of my country's aluminum industry and brake materials.

[0023] (2) The present invention uses red mud to replace copper powder in brake materials to prepare high-performance resin-based brake materials. The developed resin-based brake materials do not contain copper and other heavy metal components that are harmful to the human body, have excellent friction and wear performance, and are low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a three-dimensional response surface model diagram of the effect of changing red mud and resin content on the friction coefficient in a Box-Behnken design experiment with four factors and three levels at different temperatures.

[0025] Figure 2 This is a three-dimensional response surface model diagram of the effect of changes in red mud and resin content on wear rate in a Box-Behnken design experiment with four factors and three levels at different temperatures. DETAILED DESCRIPTION

[0026] As introduced in the background technology section, copper has excellent thermal conductivity and heat dissipation properties, and plays an important role in the friction and wear performance of resin-based brake materials working in high temperature environments. Red mud is a polluting waste residue discharged when the aluminum industry extracts alumina. It has good heat resistance. Using it as a filler to replace copper powder in brake materials can not only turn waste into treasure, but also improve the thermal decay resistance of brake materials. In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of this application is described in detail below in conjunction with specific examples.

[0027] In order to study the interaction between phenolic resin, bamboo fiber, alumina and red mud, the response surface methodology was used to study its effect on the friction coefficient. 29 experiments were designed using the Box-Behnken design experiment with four factors and three levels. The factors and corresponding levels are shown in Table 1.

[0028] Table 1 Factors and levels of Box-Behnken design experiment

[0029]

[0030] According to the 29 test formulas designed in the Box-Behnken design test table, corresponding brake material samples were prepared (the remaining raw materials were 5wt% tire powder, 3wt% graphite and 0-20wt% barium sulfate, with a total amount of 100wt%). The friction coefficient of each sample at different temperature stages was tested using an X-DM voltage-adjustable variable-speed friction testing machine. The test design and results are shown in Tables 2, 3 and 4.

[0031] Table 2 Box-Behnken design test table

[0032]

[0033]

[0034] Table 3 Box-Behnken design test friction coefficient results

[0035]

[0036]

[0037] Table 4 Box-Behnken design test wear rate results

[0038]

[0039]

[0040] The quadratic polynomial regression model in the surface response method was used to establish the nonlinear mapping relationship between the content of phenolic resin, bamboo fiber, aluminum oxide and red mud and the friction coefficient, and the friction coefficient regression model was established. The quantitative model was established between each evaluation index and the method parameters using formula (1). Where b0 is a constant; b i 、b ii and b ij are the regression coefficients of the linear term, quadratic term and interaction term respectively. i and X j are the parameters, Y are the evaluation indicators, and the stepwise regression method is used to simplify the equation.

[0041]

[0042] In order to study the interaction between various factors, Figure 1 and Figure 2 For explanation. Figure 1 The three-dimensional response surface model diagram of the effect of changes in phenolic resin (PF) and red mud (RM) content on the friction coefficient at different temperature stages can be observed. Figure 1 In (a), it can be found that along the direction of red mud content, the trend of the model is steeper than that of the resin direction, and the resin content direction is almost a horizontal transition, which means that the interaction effect on the friction coefficient in this area is mainly reflected in the influence of red mud content on the friction coefficient; Figure 1 In (b), it can be found that the trends along the red mud content and resin content are similar, which means that the friction coefficient in this area no longer changes significantly due to the change of variables. Figure 1 From (a) and (b), it can be found that when the red mud content and the resin content are both close to the middle value, the influence on the friction coefficient in the low temperature stage is most appropriate; Figure 1In (c), it can be found that the trends of red mud content and resin content are both very steep, but the trends of the two are different. The friction coefficient of red mud gradually decreases with the increase of content, while the direction of resin is opposite. Therefore, it is believed that when the contents of both tend to the middle value, it is most beneficial to the friction coefficient of the 200℃ sample; Figure 1 In (d), it can be found that the direction of red mud content and resin content is similar to Figure 1 Similar to (c), the red mud content and resin content are relatively stable in the area close to the middle value, which is similar to Figure 1 The same conclusion is drawn from (c) Figure 1 In (e), it can be found that the trend of red mud content is steeper. When its content tends to the middle value, the friction coefficient of the brake material at 300 °C is more suitable. Figure 1 In (f), it can be found that no matter red mud or resin, the two are steepest at the lowest and highest values, and the flattest at the middle value. This shows that the friction coefficient of the 350°C sample reaches a peak when the content of the two is close to the middle value, and the content at this time is the most appropriate.

[0043] from Figure 2 In (a), it can be found that the trend along the red mud content direction is steeper, the trend along the resin direction is relatively gentle, and the lower and higher stages in the red mud content direction are the steepest. Therefore, it is believed that the influence of the red mud content on the wear rate of the 100°C sample is most appropriate when it tends to the middle value; Figure 2 In (e) and (f), it can be found that the trend of red mud content increases with the increase of content, and the steepness of the resin direction is relatively gentle. Therefore, it is believed that when the red mud content is the lowest, it can affect the wear rate of the 300℃ and 350℃ samples to the greatest extent.

[0044] Overall analysis shows that the preferred contents of resin, bamboo fiber, alumina and red mud are 16.63wt%, 7.95wt%, 16.73wt% and 36.54wt%, respectively.

[0045] The regression coefficient values ​​of the established friction coefficient regression model are shown in Table 5, and the regression coefficient values ​​of the wear rate regression model are shown in Table 6.

[0046] Table 5 Regression coefficient values ​​of friction coefficient regression model

[0047]

[0048] Table 6 Regression coefficient values ​​of wear rate regression model

[0049]

[0050]

[0051] The technical solution of the present invention is further described below in conjunction with specific implementations. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0052] When the red mud used is not marked, the mesh size is 100-200 mesh.

[0053] Example 1

[0054] 1) Composition of raw materials (by mass percentage)

[0055] Red mud 35wt%, phenolic resin 15wt%, bamboo fiber 7wt%, alumina 25wt%, barium sulfate 10wt%, tire powder 5wt%, graphite 3wt%

[0056] 2) Preparation method:

[0057] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 8 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed twice; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0058] Example 2

[0059] 1) Composition of raw materials (by mass percentage)

[0060] Red mud 35wt%, phenolic resin 20wt%, bamboo fiber 7wt%, alumina 20wt%, barium sulfate 10wt%, tire powder 5wt%, graphite 3wt%.

[0061] 2) Preparation method:

[0062] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 9 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed twice; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0063] Example 3

[0064] 1) Composition of raw materials (by mass percentage)

[0065] Red mud 40wt%, phenolic resin 20wt%, bamboo fiber 5wt%, alumina 20wt%, barium sulfate 7wt%, tire powder 5wt%, graphite 3wt%.

[0066] 2) Preparation method:

[0067] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 10 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed 3 times; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0068] Example 4

[0069] 1) Composition of raw materials (by mass percentage)

[0070] Red mud 40wt%, phenolic resin 20wt%, bamboo fiber 7wt%, alumina 15wt%, barium sulfate 10wt%, tire powder 5wt%, graphite 3wt%.

[0071] 2) Preparation method:

[0072] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 10 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed 3 times; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0073] Example 5

[0074] 1) Composition of raw materials (by mass percentage)

[0075] Red mud 36.54wt%, phenolic resin 16.63wt%, bamboo fiber 7.95wt%, alumina 16.73wt%, barium sulfate 14.15wt%, tire powder 5wt%, graphite 3wt%.

[0076] 2) Preparation method:

[0077] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 8 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed twice; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0078] Comparative Example 1

[0079] 1) Composition of raw materials (by mass percentage)

[0080] Red mud 0wt%, phenolic resin 20wt%, bamboo fiber 7wt%, alumina 20wt%, barium sulfate 45wt%, tire powder 5wt%, graphite 3wt%.

[0081] 2) Preparation method:

[0082] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 8 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed twice; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0083] Comparative Example 2

[0084] 1) Composition of raw materials (by mass percentage)

[0085] Red mud 20wt%, phenolic resin 20wt%, bamboo fiber 7wt%, alumina 20wt%, barium sulfate 25wt%, tire powder 5wt%, graphite 3wt%.

[0086] 2) Preparation method:

[0087] The bamboo fiber is chopped to obtain bamboo fiber with a length of 10 mm; the resin, the sheared bamboo fiber and the tire powder are dried at 60°C for 30 minutes, and the red mud, alumina, barium sulfate and graphite are dried at 120°C for 60 minutes; the dried raw materials are put into a mixer in proportion and stirred for 8 minutes (each stirring time does not exceed 10 seconds) to mix the materials evenly; the evenly mixed mixture is put into a hydraulic press and hot-pressed at 165°C and a pressure of 10 MPa for 6 minutes, during which the exhaust is performed twice; the sample obtained by hot-pressing is heat-treated at 160°C for 12 hours and cooled with the furnace to obtain the high-performance copper-free resin-based brake material.

[0088] The brake material samples prepared in Examples 1-5 and Comparative Examples 1 and 2 were tested for friction and wear performance on an X-DM type pressure-regulated variable speed friction testing machine. According to the requirements for the fourth category of disc brake linings in the national standard for disc brake linings (GB5763-2008), the friction coefficient and wear rate of the discs at 5000 revolutions at disc temperatures of 100°C, 150°C, 200°C, 250°C, 300°C and 350°C were measured during the heating process. The results are shown in Tables 7 and 8, respectively.

[0089] Table 7 Friction coefficient test results of different samples

[0090]

[0091] aThe experimental temperature is the friction surface temperature of the testing machine disk

[0092] b The friction coefficient range includes the allowable deviation

[0093] Table 8 Wear rate test results of different samples

[0094]

[0095]

[0096] Comparative Example 1 is a control group without red mud addition, and Comparative Example 2 is a control group without red mud content protection. From the friction coefficient values ​​of Comparative Examples 1 and 2 in Table 7 at each temperature stage, it can be found that with the increase of friction temperature, the friction coefficient of the material decreases; the friction coefficient values ​​of Comparative Examples 1 and 2 at 100°C are 0.47 and 0.51 respectively, and the friction coefficient values ​​at a high temperature of 350°C are reduced to 0.28 and 0.37 respectively, indicating that the two have produced more serious thermal decay. The friction coefficients of Examples 1 to 5 at a high temperature of 350°C are basically similar to those at 100°C, among which the high temperature friction coefficients of Examples 1 and 4 are slightly higher than the friction coefficients at 100°C. Moreover, the friction coefficients and wear rates of all embodiments are within the allowable value range of the national standard (GB5763-2008).

[0097] Among them, Example 1 is compared with Example 2 to find that after changing the content of resin and alumina, the friction coefficient of Example 2 at 300-350°C is lower than that of Example 1, but its friction coefficient stability is better. Comparing Example 3 with Example 4, it can be found that after the content of alumina is changed, the friction coefficient stability of Example 4 is better than that of Example 3. Therefore, the friction coefficient and wear rate analysis of Examples 1-5 of the comprehensive response surface test are finally determined to be Example 5 as the optimized formula. Example 5 is an optimized formula obtained by analyzing the interaction between resin, bamboo fiber, alumina and red mud based on the Box-Behnken design experiment. Its friction coefficient at 100-350°C is 0.46-0.49, and the average friction coefficient is 0.48, showing good resistance to thermal decay and friction coefficient stability.

[0098] In summary, replacing copper powder with red mud can not only improve the friction performance and thermal degradation resistance of brake materials, but also realize the high added value recycling of red mud.

[0099] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A high-performance copper-free resin-based brake material prepared using red mud, characterized in that: The resin-based brake material is made of the following raw materials in percentage by mass: 30-40 wt% of red mud, 15-25 wt% of resin, 5-9 wt% of bamboo fiber, 15-25 wt% of aluminum oxide, 0-20 wt% of barium sulfate, 5 wt% of tire powder, and 3 wt% of graphite, and the sum of the percentages by mass of each raw material is 100%.

2. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The resin-based brake material is made of the following raw materials in percentage by mass: 36.54 wt% red mud, 16.63 wt% resin, 7.95 wt% bamboo fiber, 16.73 wt% alumina, 14.15 wt% barium sulfate, 5 wt% tire powder, and 3 wt% graphite, and the sum of the percentages by mass of the raw materials is 100%.

3. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The mesh size of the red mud is 100 to 200 meshes.

4. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The resin is a phenolic resin.

5. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The preparation of the resin-based brake material comprises the following steps: 1) Processing of bamboo fibers: Shearing the bamboo fibers to obtain bamboo fibers with a length of less than 20 mm; 2) Drying of raw materials: The resin, sheared bamboo fiber, and tire powder were dried at 60 °C for 30 min, and the red mud, alumina, barium sulfate, and graphite were dried at 120 °C for 60 min. 3) Evenly mix the materials: weigh the dried raw materials according to the corresponding proportions and stir them to make the materials evenly mixed; 4) Hot pressing: placing the uniformly mixed material obtained in step 3) into a mold and performing dry hot pressing; 5) Heat treatment: The sample obtained by hot pressing is heat treated at 160° C. for 12 h and cooled in the furnace to obtain the high-performance copper-free resin-based brake material.

6. The high-performance copper-free resin-based brake material prepared using red mud according to claim 5, characterized in that: Step 1) The length of the bamboo fiber is 10 mm.

7. The high-performance copper-free resin-based brake material prepared using red mud according to claim 5, characterized in that: The total stirring time in step 3) is 5 to 8 min, and each stirring time does not exceed 10 s.

8. The high-performance copper-free resin-based brake material prepared using red mud according to claim 5, characterized in that: The temperature of the hot pressing molding in step 4) is 165°C, the pressure is 10 MPa, the holding time is 6 min, and the exhaust is performed 2 to 3 times during the holding time.

9. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The friction coefficient of the resin-based brake material at 300-350° C. is above 0.

45.

10. The high-performance copper-free resin-based brake material prepared using red mud according to claim 1, characterized in that: The friction coefficient of the resin-based brake material at 300-350° C. is 0.45-0.55.

Citation Information

Patent Citations

  • A method for preparing alkaline red mud coating for preventing marine organism attachment

    CN116496680B

  • Composite material with red mud filled with polydimethylsiloxane and preparation method of composite material

    CN117304694A

  • High-content red mud hazardous waste curing filling material and preparation method thereof

    CN118479817A

  • Method for preparing composite material from red mud doped carbide slag and application

    CN118558288A

  • High-iron red mud dealkalization resource utilization process method and application thereof

    CN118563097A